The return [videorecording (DVD)] - Pasolini, Uberto; Collee, John; Bond, Edward; Fiennes, Ralph; Binoche, Juliette, 1964-; Plummer, Charlie, 1999-; Kenzari, Marwan, 1983-; Santamaria, Claudio, 1974-; Molina, Ángela; Portman, Rachel; Panduru, Marius; Homer (Decal, 2025)
After 20 years, Odysseus finally returns to Ithaca, where he finds his wife held prisoner by suitors vying to be king and his son facing death at their hands. To win back his family and all he has lost, Odysseus must rediscover his strength.